The Perceptions of International Learners Toward Teacher Code-Switching in the Elementary and Intermediate Chinese Foreign Language Classrooms - Yuqi Hu; Muhammad Afzaal; Hind Alfadda (Frontiers in Psychology, 2022)
The present study explores the perceptions of elementary and intermediate learners toward English as a code-switching medium in Chinese as a Foreign Language (CFL) classrooms. The data were collected by means of a survey of international elementary and intermediate-level students studying Chinese at the College of Chinese Language and Culture (CCLC) of Jinan University in Guangzhou, China. The data collection method included a five-point Likert scale questionnaire survey (18 closed-ended questions and one open-ended question). The analysis of quantitative and qualitative data collected from the questionnaire showed that CFL learners at both proficiency levels tended to favor code-switching in classrooms. However, the results of the Mann–Whitney U test showed that intermediate learners favored code-switching to a lesser extent than elementary learners. Moreover, their perceptions were found to differ significantly in terms of the varying functions of code-switching. These findings suggest that code-switching functions as an effective teaching strategy in the CFL classrooms, although teachers should regulate its deployment when teaching learners with different proficiency levels.